2015
DOI: 10.1111/jam.12817
|View full text |Cite
|
Sign up to set email alerts
|

A novel in vitro assay for assessing efficacy and toxicity of antifungals using human leukaemic cells infected with Candida albicans

Abstract: The assay employing Candida infection of host cell suspensions represents a promising method for testing interactions of antifungal compounds with both fungal and host cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Confocal laser scanning LIVE/DEAD â staining of RHE RHE samples from each time point were placed on microscope slides and 100 ll of LIVE/DEAD â stain (containing 25 lmol l À1 SYTO â 9 and 15 lmol l À1 propidium iodide) applied directly to the tissue, as previously described (Boros-Majewska et al 2015). Treated samples were incubated for 30 min at 37°C in the dark prior to transfer to clean glass slides.…”
Section: Hyphal Invasion Assaymentioning
confidence: 99%
“…Confocal laser scanning LIVE/DEAD â staining of RHE RHE samples from each time point were placed on microscope slides and 100 ll of LIVE/DEAD â stain (containing 25 lmol l À1 SYTO â 9 and 15 lmol l À1 propidium iodide) applied directly to the tissue, as previously described (Boros-Majewska et al 2015). Treated samples were incubated for 30 min at 37°C in the dark prior to transfer to clean glass slides.…”
Section: Hyphal Invasion Assaymentioning
confidence: 99%
“…Furthermore, it was shown to be higher than the uninfected control. 22 There was a significant difference in the number of inflammatory cells between the negative and positive control groups. The significant difference between the results of the holothurin treatment given directly to the Wistar vagina revealed that it was lower than the administration of caspofungin.…”
Section: Discussionmentioning
confidence: 91%
“…The viability of neutrophils upon exposure to yeasts is an important indication on the type of NETosis, lytic or non-lytic ( Yang et al., 2016 ; Papayannopoulos, 2018 ). In this work, we quantified the neutrophils’ viability using a trypan blue exclusion assay, and although there are other quantification methodologies considered more reliable and sensitive ( Hosseinzadeh et al, 2012 ; Boros-Majewska et al., 2015 ), the robustness and consistency of the results justifies its validity. This observation reinforces the idea that yeasts induce a non-lytic NETosis, at least in the cases of C. albicans and C. glabrata .…”
Section: Discussionmentioning
confidence: 99%